Mixed vitiligo of Blaschko lines: a newly discovered presentation of vitiligo responsive to combination treatment. Issue 4 (11th March 2016) - Kovacevic, Maja; Stanimirovic, Andrija; Vucic, Majda; Goren, Andy; Situm, Mirna; Lukinovic Skudar, Vesna; Lotti, Torello
ABSTRACT: Vitiligo, depigmenting disorder of the skin and mucous membranes, affects up to 1% of the population worldwide. It is classified into four major types: segmental, non‐segmental, mixed, and unclassified type. Non‐segmental vitiligo refers to non‐dermatomal distribution of lesions, while dermatomal distribution of lesions is present in patients with segmental vitiligo. Segmental vitiligo can also follow Blaschko lines – pathways of epidermal cell migration and proliferation during the development of the fetus. Here, we present patient with segmental and non‐segmental vitiligo following Blaschko lines with excellent therapeutic response to combined therapy. Prior to our report, a case of segmental and non‐segmental vitiligo followed by Blaschko lines was never described, therefore we suggest the term "mixed vitiligo of Blaschko lines" to describe this entity. This is also a rare case in which 90% repigmentation was achieved in patient with segmental and nonsegmental vitiligo following Blaschko lines in only 2 months of combined therapy.